IMPLEMENTASI ALGORITMA BOYER-MOORE DAN BRUTE FORCE UNTUK PENCARIAN TAFSIR DI ENSIKLOPEDIA AL-QUR’AN BERBASIS WEBSITE: MPLEMENTATION OF BOYER-MOORE AND BRUTE FORCE ALGORITHMS FOR TAFSIR SEARCH IN A WEB-BASED QUR’ANIC ENCYCLOPEDIA - Siti Nadilla; Rizal Tjut Adek; Rizki Suwanda (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
The growing demand for structured and efficient access to Qur’anic content based on specific themes underscores the need for a thematic search system for verses and tafsir. This study aims to develop a web-based Qur’anic encyclopedia featuring a keyword-based search function that employs string matching algorithms. We implemented and compared two algorithms Boyer-Moore and Brute Force to assess their performance in processing large textual tafsir datasets. The system was built using PHP and MySQL, utilizing a dataset comprised of categorized tafsir and verses according to themes. Our methodology included a literature review, interface design, system development, algorithm implementation, and performance testing. The results indicate that the Boyer-Moore algorithm is significantly faster and more efficient than the Brute Force algorithm for large-scale text searches. Testing with ten different keywords revealed that the average search time for the Boyer-Moore algorithm was 0.030 seconds, while the Brute Force algorithm took 0.069 seconds, making Boyer-Moore approximately 56% faster. The search feature reliably retrieved relevant verses and tafsir based on user input. Additionally, the system demonstrated user-friendliness through a responsive web interface. These findings highlight the effectiveness of string matching algorithms in digital Islamic tools and emphasize the advantage of the Boyer-Moore algorithm in optimizing the complexity of thematic Qur’anic searches.